2019
DOI: 10.1371/journal.pone.0218595
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis of accelerometer-measured sleep, physical activity, and sedentary time and differences in health characteristics in adult women

Abstract: Objectives Independently, physical activity (PA), sedentary behavior (SB), and sleep are related to the development and progression of chronic diseases. Less is known about how rest-activity behaviors cluster within individuals and how rest-activity behavior profiles relate to health. In this study we aimed to investigate if adult women cluster into profiles based on how they accumulate rest-activity behavior (including accelerometer-measured PA, SB, and sleep), and if participant characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Future longitudinal studies could identify trajectories/profiles of 24-h time-use behaviors (see e.g. [ 92 ]) and study their associations with other lifestyle choices.…”
Section: Discussionmentioning
confidence: 99%
“…Future longitudinal studies could identify trajectories/profiles of 24-h time-use behaviors (see e.g. [ 92 ]) and study their associations with other lifestyle choices.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of previous studies examining profiles or phenotypes of activity in adult populations using LCAs of objectively measured activity data. Prior studies have examined variations in activity during waking hours (29)(30)(31), or activity-sleep patterns during a 24-hour period (32). All of these studies identified distinct activity profiles (3 to 6 profiles) for time spent in different types or intensity when awake, with 1 identifying a distinct profile of poor sleepers.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are a limited number of studies outlining variations in patterns of 24-hour activity and sleep within defined adult health populations using objective measures (29)(30)(31)(32). To the best of our knowledge, no previous study has examined how objectively measured 24-hour activity and sleep profiles may vary in adults with arthritis.…”
mentioning
confidence: 99%
“…Model-based approaches that could segment physicians into different phenotype groups may allow for tailoring of behavioral interventions to improve patient care. For example, latent class analysis has been used to classify phenotypes using clinical [5,6], behavioral [7,8], and activity data [9,10].…”
Section: Introductionmentioning
confidence: 99%